2003
DOI: 10.1046/j.1460-9568.2003.02689.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between mesocortical dopamine release and fear‐related behaviours in two psychogenetically selected lines of rats that differ in coping strategies to aversive conditions

Abstract: The mesocortical and mesolimbic dopaminergic (DAergic) pathways are activated by either aversive or rewarding stimuli. The functional tone of these DAergic neurons also increases during the execution of cognitive tasks. The present study was designed to examine the relationship between mesocortical and mesolimbic DAergic function and the expression of fear-related behaviours as compared with attention- and cognition-related mechanisms (e.g. coping strategies), in response to aversive conditions. To this aim, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
75
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 59 publications
12
75
0
Order By: Relevance
“…Moreover, the relationship between monoamine levels and impulsivity depends on the particular impulsive behavior evaluated (Winstanley et al, 2006, for review). Convergent evidence suggests that monoaminergic (at least DA and 5-HT) functional differences in the mesolimbic-mesocortical systems and related areas mediate the impulsivity-related behavioral traits that distinguish the Roman rat lines/ strains, including differential sensitivity to the effects of (and preference for) drugs of abuse (for reviews, see Charnay et al, 1995;Driscoll et al, 1980;Fattore et al, 2009;Fernández-Teruel et al, 2002a;Giorgi et al, 1994Giorgi et al, , 2003Giorgi et al, , 2007Guitart-Masip et al, 2006a, b, 2008aKulikov et al, 1995;Lecca et al, 2004). Collectively, the neurochemical findings reported in these studies suggest a relatively increased function (or tone) of DA and 5-HT neurotransmission in the RHA rat line/strain relative to RLA animals.…”
Section: Increased Adjunctive Drinking Acquisition In Rha-i Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the relationship between monoamine levels and impulsivity depends on the particular impulsive behavior evaluated (Winstanley et al, 2006, for review). Convergent evidence suggests that monoaminergic (at least DA and 5-HT) functional differences in the mesolimbic-mesocortical systems and related areas mediate the impulsivity-related behavioral traits that distinguish the Roman rat lines/ strains, including differential sensitivity to the effects of (and preference for) drugs of abuse (for reviews, see Charnay et al, 1995;Driscoll et al, 1980;Fattore et al, 2009;Fernández-Teruel et al, 2002a;Giorgi et al, 1994Giorgi et al, , 2003Giorgi et al, , 2007Guitart-Masip et al, 2006a, b, 2008aKulikov et al, 1995;Lecca et al, 2004). Collectively, the neurochemical findings reported in these studies suggest a relatively increased function (or tone) of DA and 5-HT neurotransmission in the RHA rat line/strain relative to RLA animals.…”
Section: Increased Adjunctive Drinking Acquisition In Rha-i Ratsmentioning
confidence: 99%
“…Abundant evidence implicates dopaminergic mechanisms in these differences. Compared with RLA rats, RHA rats show different dopaminergic responses: activation in the mesocortical dopaminergic pathway by stressors and anxiogenic drugs (Giorgi et al, 2003); more rapid baseline turnover rate of dopamine (DA) in the caudate nucleus (Driscoll et al, 1990); and more intense stereotypy in response to acute challenge with the DA receptor agonist apomorphine (Giménez-Llort et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been hypothesized that long-term exposure to drugs of abuse may alter the functional activity of dopaminergic afferent projections and glutamatergic neurons in frontocortical areas, with a consequent deficiency in the ability to inhibit inappropriate responses to drugs or drug-paired stimuli (Jentsch and Taylor, 1999;Everitt and Wolf, 2002;Chambers et al, 2003;Vanderschuren and Everitt, 2005). It is therefore noteworthy in this context that, compared with RLA rats, the mesocortical dopaminergic system of RHA rats is more robustly activated by both stressful and rewarding stimuli (D'Angio et al, 1988;Corda et al, 1997;Giorgi et al, 1999Giorgi et al, , 2003. In addition, RHA rats display higher scores than RLA rats in experimental paradigms used to assess sensation/ novelty seeking behavior in rodents (Siegel et al, 1993;Escorihuela et al, 1999;Fernández-Teruel et al, 2002;Steimer and Driscoll 2005).…”
Section: Figurementioning
confidence: 99%
“…Thus, compared with their RLA counterparts, RHA rats display a more robust sensation/novelty seeking profile, as well as higher baseline levels of impulsivity, and a marked preference for and intake of natural and drug rewards (Zeier et al, 1978;Siegel et al 1993;Escorihuela et al 1999;Giorgi et al 1999;Fernández-Teruel et al 2002). The phenotypic traits that distinguish these lines are at least partly determined by differences in the functional properties of their central dopaminergic pathways: (1) stressors and anxiogenic drugs activate the mesocortical dopaminergic projection of RHA, but not RLA, rats (D'Angio et al, 1988;Corda et al, 1997;Giorgi et al, 2003); (2) RHA rats have a higher density of D-1 dopamine (DA) receptors in the NAc (Giorgi et al, 1994); (3) the acute administration of psychostimulants and morphine causes a larger increment in motor activity and in DA output in the shell than in the core of the NAc of RHA, but not RLA, rats (Lecca et al, 2004); (4) the repeated administration of psychostimulants and morphine induces behavioral sensitization only in RHA rats Corda et al, 2005;Giorgi et al, 2005a); (5) in sensitized RHA rats, a subsequent challenge with these drugs elicits a more robust increment in DA output in the NAc-core, associated with an attenuated dopaminergic response in the NAc-shell, whereas these adaptive changes are not observed in sensitization-resistant RLA rats (Giorgi et al, 2005b(Giorgi et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that RLA rats represent a valid genetic model to investigate the neural circuitry and molecular mechanisms underlying stress‐induced depression and, more specifically, to study depression associated with anxiety symptoms. Multidisciplinary studies aimed at identifying the central neuronal circuits involved in the above‐mentioned behavioral differences across the Roman lines have shown that their divergent phenotypic traits may be accounted for, at least in part, by differences in the functional responses of their central monoaminergic systems (D'Angiò, Serrano, Driscoll, & Scatton, 1988; Giorgi, Lecca, Piras, Driscoll, & Corda, 2003; Giorgi, Piras, Lecca, & Corda, 2005; Giorgi et al., 1994; Giorgi, Piras, et al., 2003 Giorgi et al., 2007, 2015; Lecca, Piras, Driscoll, Giorgi, & Corda, 2004; Sanna et al., 2015; Tournier et al., 2013). …”
Section: Introductionmentioning
confidence: 99%